Differences between national and international guidelines for the management of diabetic foot disease. Issue 2 (20th December 2018) - Parker, Christina N.; Van Netten, Jaap J.; Parker, Tony J.; Jia, Limin; Corcoran, Heidi; Garrett, Michele; Kwok, Ching F.; Nather, Aziz; Que, Ma. Teresa; Srisawasdi, Gulapar; Wraight, Paul; Lazzarini, Peter A.
Abstract: Aim: No studies have investigated if national guidelines to manage diabetic foot disease differ from international guidelines. This study aimed to compare guidelines of Western Pacific nations with the International Working Group on the Diabetic Foot (IWGDF) guidance documents. Methods: The 77 recommendations in five chapters of the 2015 IWGDF guidance documents were used as the international gold standard reference. The IWGDF national representative(s) from 12 Western Pacific nations were invited to submit their nation's diabetic foot guideline(s). Four investigators rated information in the national guidelines as "similar, " "partially similar, " "not similar, " or "different" when compared with IWGDF recommendations. National representative(s) reviewed findings. Disagreements in ratings were discussed until consensus agreement achieved. Results: Eight of 12 nations (67%) responded: Australia, China, New Zealand, Taiwan, and Thailand provided national guidelines; Singapore provided the Association of Southeast Asian Nations guidelines; and Hong Kong and the Philippines advised no formal national diabetic foot guidelines existed. The six national guidelines included were 39% similar/partially similar, 58% not similar, and 2% different compared with the IWGDF recommendations. Within individual IWGDF chapters, the six national guidelines were similar/partially similar with 53% of recommendations for the IWGDF prevention chapter, 42% for wound healing, 40% for infection, 40% for peripheral artery disease, and 20% for offloading. Conclusions: National diabetic foot disease guidelines from a large and diverse region of the world showed limited similarity to recommendations made by international guidelines. Differences between recommendations may contribute to differences in national diabetic foot disease outcomes and burdens.